Uso de modelos para estimativa do saldo de radiação solar em ambiente de floresta tropical na Amazônia - JIMENES, Alfredo Cesar Gonçalves (2022)
The present work has as its study area a sample of the National Forest of Caxiuanã, located in the municipality of Melgaço, state of Pará, in the east of the Amazon. The meteorological information was obtained from the ESECAFLOR project. The experiment area is located at coordinates 1° 44' 12.6942" S latitude, and 51° 27' 43.0049" W longitude, approximately 15 m above the mean sea level, where there is an automatic meteorological station, installed next to the top of a 40 m high micrometeorological tower among the trees. Data on global solar radiation, air temperature and relative humidity and net radiation were obtained by sensors. The records were made at 30-minute intervals and stored in a datalogger, from January 1 to December 31, 2019. Based on this information, the Allen and Brunt-Penman methods were used to estimate the net radiation and for means of statistical analysis to determine the method with the best application in the study area, as well as the one that presented the highest correlation between the measured and the estimated. Key words: estimation model; solar radiation; forest.